2010
DOI: 10.1099/vir.0.019240-0
|View full text |Cite
|
Sign up to set email alerts
|

Punique virus, a novel phlebovirus, related to sandfly fever Naples virus, isolated from sandflies collected in Tunisia

Abstract: Sandflies are widely distributed around the Mediterranean Basin. Therefore, human populations in this area are potentially exposed to sandfly-transmitted diseases, including those caused by phleboviruses. Whilst there are substantial data in countries located in the northern part of the Mediterranean basin, few data are available for North Africa. In this study, a total of 1489 sandflies were collected in 2008 in Tunisia from two sites, bioclimatically distinct, located 235 km apart, and identified morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 34 publications
6
72
1
2
Order By: Relevance
“…For this study the 3 virus strains were (i) Toscana virus strain MRS2010-4319501 [13], (ii) Punique virus strain Tunisia2009T101 [7], (iii) Sandfly fever Sicilian virus strain Sabin [14]. The plate was incubated at 37°C for one hour, then a 100 μL volume of Vero cells containing approximately 2.10 4 cells in 5% foetal bovine serum was added to each well, and incubated at 37°C in presence of 5% CO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study the 3 virus strains were (i) Toscana virus strain MRS2010-4319501 [13], (ii) Punique virus strain Tunisia2009T101 [7], (iii) Sandfly fever Sicilian virus strain Sabin [14]. The plate was incubated at 37°C for one hour, then a 100 μL volume of Vero cells containing approximately 2.10 4 cells in 5% foetal bovine serum was added to each well, and incubated at 37°C in presence of 5% CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A recent sero-epidemiological study conducted in the governorate of Bizerte (northern Tunisia) showed that both Toscana and Punique viruses could infect human populations although Toscana virus was much more prevalent than Punique virus [5]. In Tunisia, Toscana, Punique and Utique viruses were detected and/or isolated from Phlebotomus pernicious and Phlebotomus longicuspis, which are considered as possible vectors of phleboviruses [2,7]. Both sandfly species are also the main vectors of Leishmania infantum, etiologic agent of zoonotic visceral leishmaniasis (ZVL) in Tunisia [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among the SFVs, only TOSV is related to neuro-invasive disease, while other sand-fly variants cause a mild flu-like illness, but the serological differentiation between the serotypes is very difficult and they are usually regarded as one serocomplex. In recent years, the geographical distribution of TOSV (or closely related other phleboviruses) has been extended dramatically within the old world and antigenically similar novel viruses have been reported [2,[15][16][17][18]. Therefore, our cases might represent a TOSV-related neuro-invasive strain, even though the immunofluorecsence assays were unable to distinguish between the viruses within the sand-fly virus serocomplex.…”
Section: Discussionmentioning
confidence: 90%
“…4 Recently, molecular evidence showed the presence of two distinct phleboviruses closely related to SFSV in Algeria and Tunisia. 15,16 Nucleic acids detected in this study within positive samples shared approximately 99% nucleotide sequence identity with strains that were associated with human illness in Cyprus and Turkey in 2008, implicating a possible Eastern Mediterranean origin of the Ethiopian strain of SFSV.…”
Section: Discussionmentioning
confidence: 99%